The Functional Assessment of Cancer Therapy – General (FACT-G) is valid for monitoring quality of life in non-Hodgkin lymphoma patients - Yost, KJ (2012)
Quality of life (QoL) is an important outcome in patients with non-Hodgkin lymphoma (NHL). We assessed the validity of administering the Functional Assessment of Cancer Therapy – General (FACT-G) at 12-month intervals over 3 years in a longitudinal study of 611 prospectively enrolled, newly diagnosed NHL patients. We evaluated corrected item-total correlation and percent missing to identify items that may be less useful in certain NHL patient subgroups. The FACT-G subscales and total score demonstrated good internal consistency reliability, convergent validity and known-groups validity. Most scores also demonstrated good responsiveness to change. Questions that could be problematic included GE3 (losing hope) and GP2 (nausea) for patients in remission, and GP5 (bothered by side effects) for patients being observed. Overall, the FACT-G was a valid measure for monitoring QoL over time in NHL patients. However, sensitivity analyses based on subscale scoring that excludes potentially problematic items may be warranted.